Relationship of work environment and application of Occupational health and safety on biology laboratory technician work productivity - Muhsin Muhsin (Jurnal Pijar Mipa, 2022)
This study aimed to determine the simultaneous and partial effect of training variables, work environment, and occupational safety and health (OHS) application on the work productivity of laboratory technicians at University of Mataram, Indonesia. The type of research is explanatory research using a quantitative approach. Respondents in the study are 39 people. The data used in this study is taken using a questionnaire. Data were analyzed using multiple linear regression with the help of SPSS version 20.00 for windows. The results showed that: (1) training, work environment, and the application of OHS had a positive and significant effect simultaneously on the work productivity of the laboratory technicians, (2) training, the work environment, and the application of OHS had a positive and significant partial effect on the work productivity of the laboratory technicians, and (3) training is a variable that has a dominant influence on the work productivity of laboratory technicians at University of Mataram.